Ethnic differences in knowledge, attitudes, and practices related to dietary salt intake and association with hypertension in Malaysia: a multi-centre cross-sectional study - Chia, Yook Chin; Ching, Siew Mooi; Chew, Ming Tsuey; Devaraj, Navin Kumar; Oui, Jethro Ee Keat; Lim, Hooi Min; Chew, Bee Nah; Mohamed, Mohazmi; Ooi, Pei Boon; Cheng, Maong Hui; Beh, Hooi Chin; Chung, Felicia Fei-Lei (Springer Nature, 2024)
The association between high salt intake and elevated blood pressure levels has been well-documented. However, studies on how effectively this knowledge translates into actionable practices, particularly across different ethnic groups, remain limited. This study aimed to evaluate the knowledge, attitudes, and practices (KAP) towards dietary salt intake across ethnicities and determine its association with hypertension. 5128 Malaysian adults recruited from a national blood pressure screening study completed questionnaires on demographics, and KAP related to dietary salt intake. There were 57.4% Malay, 23.5% Chinese, 10.4% Indian, and 8.7% individuals of other ethnic groups. Overall, more than 90% of the participants knew that a high salt intake causes serious health problems, but only around one-third knew the relationship between high salt intake and strokes and heart failure. Participants of different ethnic groups displayed significant differences in the KAP domains, where Indians generally exhibited better knowledge, attitudes, and reported better practices such as reading salt labels and using spices. Those who were unaware of the difference between salt and sodium and who reported not reading salt labels had higher odds of having elevated blood pressure. These findings demonstrate that while there is a suboptimal translation of salt knowledge into practice in Malaysia, with significant differences in KAP observed between ethnic groups, the potential of improving health outcomes by improving the clarity and awareness of salt labels is substantial. Tailored education promoting salt-label reading, minimizing processed foods intake and discretionary salt use should be ethnic-specific to better curb this escalating hypertension epidemic.